Genotoxic and Cytotoxic Activities of Cornhusk Extract of Zea mays and Leaf Extract of Sacharum officinarum - Akpan, Emem Eyo; Anagboso, Martin Osita; Johnny, Imoh Imeh; Ebong, Nwakaego Omonigho; Okokon, Jude Efiom (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Zea mays husk and Saccharum officinarum have been used for years in ethnomedicine for their antimalarial, anti-inflammatory, antipyretic, antidiabetic, and antiphlogistic activities. The cytotoxic and genotoxic effects of Zea mays husk and Saccharum officinarum leaf extracts on the root meristem cells of Allium cepa were investigated. Onion bulbs were exposed to 2.5 mg/ml, 5mg/ml, and 10 mg/ml concentrations of the extracts for macroscopic and microscopic analysis. Tap water was used as a negative control and Methotrexate (0.1 mg/ml) was used as a positive control. There was statistically significant (p < 0.05) inhibition of root growth depending on concentration by the extracts when compared with the negative control group. All the tested extracts were observed to have cytotoxic effects on cell division in A. cepa. The extract induced chromosomal aberrations and micronuclei (MNC) formations in A. cepa root tip cells were significant (p<0.05) when compared with the control group. The extracts treatment further induced cell death, ghost cells, cells membrane damage, and binucleated cells. The Zea mays husk extract was found to exhibit higher cytotoxic and genotoxic potential than Saccharum officinarum leaf extract. These results suggest that Zea mays husk and Saccharum officinarum leaf extracts possess cytotoxic and genotoxic effects on A. cepa.